Livelihood Diversification and Women’s Economic Participation in Dupcheshwor Rural Municipality, Nuwakot, Nepal - Thapa, Raj Kumar (Victoria Journal of Management, 2025)
This study examines women’s economic participation and livelihood diversification in Dupcheshwor Rural Municipality, Nuwakot, Nepal, with a focus on their involvement in various economic activities, including agriculture, livestock rearing, small-scale businesses, and wage labor. Using a mixed-methods approach that combines quantitative surveys from 200 households with qualitative insights from interviews and focus group discussions, the research reveals that agriculture remains the primary income source. However, women significantly enhance household income through diversified livelihoods, highlighting their vital role in ensuring household stability. Key factors influencing women's participation in economic activities include education, access to land, household responsibilities, and social norms. Women with higher education levels are more likely to pursue non-traditional occupations. Despite their essential contributions, women face numerous barriers that limit their economic potential, including limited access to resources, societal expectations, and the burden of domestic responsibilities. The study points out the need for immediate policies aimed at empowering women by enhancing access to education, financial resources, and community support structures. In conclusion, the findings emphasize the importance of initiatives that strengthen women’s economic roles, promote gender equality, and improve overall household welfare in rural contexts. Addressing these barriers and recognizing women’s economic capabilities enables the creation of inclusive and equitable local economies, ensuring that women’s contributions are fully acknowledged and leveraged for broader social and economic progress.